Priority Selection Within National Innovation Strategy in Global Context - Prokopenko Olha; Omelyanenko Vitaliy (Economics and Business)
The article deals with global experience in analysing the priorities based on their importance for country development and on national and international criteria using algorithm for the selection process. The main aspects of the process of development and implementation of international technology strategies were considered. The authors prove that through the analysis of innovation systems at macro level decision about the priorities in optimization with the aim to improve regulations in science, technology and innovation is provided. The main techniques and decisions were considered based on foresight-studies. Authors propose to create informative and analytical system for the foresight aims.